A Phase 1 Study to Evaluate the Pharmacokinetics and Safety of Cabotegravir in Patients With Hepatic Impairment and Healthy Matched Controls. Issue 5 (27th February 2019) - Shaik, Jafar Sadik B.; Ford, Susan L.; Lou, Yu; Zhang, Zhiping; Bakshi, Kalpana K.; Tenorio, Allan R.; Trezza, Christine; Spreen, William R.; Patel, Parul
Abstract: Cabotegravir is an investigational integrase inhibitor in development for the treatment and pre‐exposure prophylaxis of HIV‐1 infection. Liver disease is a major cause of morbidity and mortality in HIV‐infected individuals and can impact the pharmacokinetics (PK) of HIV medications. This phase 1 study evaluated the PK of cabotegravir in individuals with moderate hepatic impairment (n = 8) versus healthy controls (n = 8). Participants received a single oral cabotegravir 30‐mg tablet and underwent PK sampling to determine total and unbound plasma cabotegravir concentrations. Calculated geometric least‐squares mean ratios (90% confidence intervals) for individuals with hepatic impairment versus healthy controls were 0.73 (0.50‐1.06) for AUC0‐∞, 0.69 (0.51‐0.93) for Cmax, 1.40 (0.80‐2.46) for unbound concentration (CU) 2 hours postdose, 1.55 (0.82‐2.94) for CU at 24 hours, 2.14 (1.57‐2.90) for unbound fraction (FU) at 2 hours, and 1.90 (1.14‐3.18) for FU at 24 hours. Adverse events (AEs) occurred in 2 individuals with hepatic impairment and 3 healthy controls and were grade 1/2 in severity. No participant discontinued because of AEs. Increased FU resulted in a modest decrease in total plasma exposure not considered clinically relevant. We conclude that cabotegravir may be administered without dose adjustment in patients with mild to moderate hepatic impairment.